Fragmented care and chronic illness patient outcomes: A systematic review - Jee Young Joo (Wiley, 2023)
Abstract Aim This systematic review examined recent studies on fragmented care of patients with chronic illnesses in the United States to examine the association between fragmented care and patient outcomes. Design Systematic review. Methods Studies published from January 1, 2012, to June 1, 2022, were selected from four electronic databases (PubMed, CINAHL, PsycINFO, and Web of Science), following the Cochrane protocols and PRISMA statements. Based on inclusion and exclusion criteria, ten studies that examined associations published between 2015 and 2021 were selected. A methodological assessment was conducted with the Quality Assessment Tool for Observational Cohort and Cross‐Sectional Studies. The studies selected for this systematic review were rated as having fair methodological rigor. The protocol of this review was registered in the International Prospective Register of Systematic Reviews (PROSPERO registration number: CRD42021285379). Because of the heterogeneity of the selected studies' data, a systematic narrative synthesis of the extracted data was conducted. Results Three common measures for fragmented care and outcomes were synthesized. A synthesis of the studies found significant association between fragmented care and adverse outcomes of chronic illnesses (emergency department visits, utilization of diagnostic tests, and healthcare costs). Despite the heterogeneity of significant findings between fragmented care and patient outcomes, the relationship between these outcomes and fragmented care was significant. This systematic review provides clear evidence of the association between care fragmentation and its adverse effects on individuals with chronic illnesses. However, mixed relationship findings were also reported. Conclusion Given the demands of overcoming fragmented care in healthcare settings in the United States, nurse managers, healthcare leaders, and policymakers should utilize this evidence to reduce fragmented care strategies. It is recommended that nurse researchers and other healthcare practitioners conduct further studies to understand the contexts and mechanisms of fragmented care and develop theoretical frameworks for care fragmentation and chronic illness outcomes.